Asset prices, collateral, and unconventional monetary policy in a DSGE model - Björn Hilberg; Josef Hollmayr (Deutsche Bundesbank, 2013)
In this paper we set up a New-Keynesian model with a heterogenous banking sector to analyze liquidity problems on the interbank market. The presence of an interbank market is essential to consider a situation where an increased liquidity supply by the central bank is only partially passed on to the interbank market. Moreover, this framework allows us to examine the implications of an unconventional monetary policy tool modeled as a haircut rule applied to eligible assets in repurchase agreements ('Repos') on the interbank market. We can show that this tool is suited to bring down the interest rate charged among banks on the interbank market. Furthermore an exogenous bubble process is modeled to evaluate the effects of the haircut rule for a central bank which decides to implement a 'leaning-against-the- wind'-policy. Finally, we analyze the long-run consequences of reacting to asset price movements and examine the effects of different exit strategies. We find that the central bank can stabilize all variables at the cost of higher inflation and that macroeconomic volatility is smallest if the central bank communicates the exit date in advance and credibly commits to it.
Keywords: E4; E5; E61; G21; 330; New-Keynesian Model; Monetary Policy; Business Cycle; Collateral; Haircuts